2019
DOI: 10.2196/14303
|View full text |Cite
|
Sign up to set email alerts
|

Mechanisms of Social Media Effects on Attitudes Toward E-Cigarette Use: Motivations, Mediators, and Moderators in a National Survey of Adolescents

Abstract: Background Exposure to risk behavior on social media is associated with risk behavior tendencies among adolescents, but research on the mechanisms underlying the effects of social media exposure is sparse. Objective This study aimed to investigate the motivations of social media use and the mediating and moderating mechanisms of their effects on attitude toward electronic cigarette (e-cigarette) use among adolescents. Methods Using data from … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
24
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 50 publications
(27 citation statements)
references
References 48 publications
0
24
0
Order By: Relevance
“…Time and frequency are often used to measure the regularity of social media use [ 51 ]. We attempted to draw an explanation from previous studies that investigated the relationship between social media use frequency and behavioral outcomes; we found that “frequency” may be a direct indicator of the motivations of social media use, such as self-expression, social learning, social comparison, or filtering [ 52 , 53 ]. Therefore, we cautiously concluded that frequency of social media use indicates the degree of engagement or investment in social media.…”
Section: Discussionmentioning
confidence: 99%
“…Time and frequency are often used to measure the regularity of social media use [ 51 ]. We attempted to draw an explanation from previous studies that investigated the relationship between social media use frequency and behavioral outcomes; we found that “frequency” may be a direct indicator of the motivations of social media use, such as self-expression, social learning, social comparison, or filtering [ 52 , 53 ]. Therefore, we cautiously concluded that frequency of social media use indicates the degree of engagement or investment in social media.…”
Section: Discussionmentioning
confidence: 99%
“…Hip Hop and Popular adolescents and current vape users also reported extensive smartphone and social media use, in particular the use of Instagram, Snapchat, sports analysis sites, and video/music streaming services. Heavy social media use may contribute to adolescent vaping as user- and industry-generated vaping content abounds across platforms, 70-74 and early research suggests that heavier social media use and exposure to vape advertisements on social media are associated with willingness and intentions to vape. 75 Given the known association between exposure to online tobacco marketing and adolescent tobacco initiation and progression, 76,77 heavy social media use among Hip Hop and Popular adolescents may further explain why these youth vape.…”
Section: Discussionmentioning
confidence: 99%
“…A framework of multilevel influences, first created by Urie Bronfenbrenner (1977), later identified five distinct social sources of behavioural influence: intrapersonal, interpersonal, organisational/institutional, community, and policy (McLeroy et al, 1988). While most studies about e-cigarettes have examined the influence of intrapersonal factors such as peers’ attitudes towards e-cigarettes (Cho et al, 2019), interpersonal factors (e.g. family) (Fite et al, 2018), or public policy (Friedman et al, 2019), few studies have explored behavioural strategies at the organisational- or community-levels of the social ecological model.…”
Section: Introductionmentioning
confidence: 99%